The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0103-33522013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Modelando a participação social: uma análise da propensão à inserção em instituições participativas, a partir de características socioeconômicas e políticas

Abstract: Modelando a participação social: uma análise da propensão à inserção em Instituições Participativas, a partir de características socioeconômicas e políticas Modeling social participation: an analysis of the propensity of individuals to get inserted in participatory processes, based upon socioeconomic and political characteristicsRevista Brasileira de Ciência Política, nº10. Brasília, janeiro -abril de 2013, pp. 63-106. * É doutorando em Ciência Política na Universidade Federal de Minas Gerais (Belo Horizonte, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
31

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 13 publications
0
1
0
31
Order By: Relevance
“…A nationwide study on social participation showed that less than 3% of 2,200 respondents participate in public policy councils, for example Health and Education Councils, among others (Vaz, 2013). The case study of Rio de Janeiro state councils and conferences (Guizardi, 2015) showed that the current framework of representativeness of health councils, specifically in Rio de Janeiro, is not directly articulated to active movements and entities of civil society.…”
Section: Resultsmentioning
confidence: 99%
“…A nationwide study on social participation showed that less than 3% of 2,200 respondents participate in public policy councils, for example Health and Education Councils, among others (Vaz, 2013). The case study of Rio de Janeiro state councils and conferences (Guizardi, 2015) showed that the current framework of representativeness of health councils, specifically in Rio de Janeiro, is not directly articulated to active movements and entities of civil society.…”
Section: Resultsmentioning
confidence: 99%
“…Para o autor, as participações nessas instituições são limitadas também pois as reuniões têm uma periodicidade específica; o que exige tempo do integrante para se dedicar à atividade; e os temas tratados exigem compreensão e estudo, uma vez que delineam diretrizes e/ou normas para a área temática, gerando receios por parte dos indivíduos cujo engajamento esteja radicalmente fora de seus padrões e/ou expectativas. "Portanto, os indivíduos podem, na verdade, sequer se sentir como parte efetiva dos processos políticos" (VAZ, 2013 A representação tripartite do Conselho também falha na representação dos usuários, uma vez que apenas prevê assentos para a AGESPISA (concessionária pública dos serviços de saneamento) e representantes dos comitês, mas não prevê vagas direcionadas as categorias dos usuários. Com relação a gestão de águas subterrâneas, vale citar também a não existência de uma câmara técnica especifica para o assunto, como acontece nos Conselhos Nacional Conselho Nacional de Recursos Hídricos.…”
Section: Fraquezas (Weakness)unclassified
“…Por seu desenho institucional permitir, em geral, a vocalização das demandas dos territórios locais, os OP podem desempenhar importante papel quanto à ampliação do direito à cidade (Lefebvre 1991). Isso porque diferentemente dos Conselhos de Políticas Públicas e das Conferências Temáticas, os OP oportunizam maior inclusão dos setores mais pobres, menos escolarizados e da raça/etnia negra (Ação educativa IBOPE, 2003;Vaz 2013).…”
Section: Introductionunclassified